Development of lower limb stiffness and its contribution to maximum vertical jumping power during adolescence - Korff, T.; Horne, S. L.; Cullen. S. J.; Blazevich, A. J. (The Journal of Experimental Biology, 2009)
Maximum power production during multi-joint tasks increases as children grow older. Previous research suggests that in adults, maximum power production in jumping is related to lower limb stiffness. In a developmental context, the question arises as to whether the relationship between maximum power production and lower limb stiffness is age-dependent. The purpose of this study was to investigate the relationship between lower limb stiffness and peak power production in adolescents (AD) and preadolescents (PA). With institutional approval, two groups of pre-adults (pre-adolescents: 11-13 years of age, N 43; adolescents: 16-18 years of age, N 30) performed 30 two-legged hops at their preferred frequency and three maximum counter-movement jumps. AD produced significantly greater peak power during the counter-movement jump than PA (t71 -5.28, P<0.001) even when body mass was accounted for. Lower limb stiffness was significantly correlated with peak power production during the countermovement jump in AD (R 0.62, P<0.001) but not in PA (R 0.26, P 0.10). When normalised to body mass, the relationship between lower limb stiffness and peak power also differed between the two age groups (R 0.30, P 0.11 for AD and R 0.02, P 0.88 for PA). In addition, we found that during hopping, both PA and AD behaved like a simple spring-mass system. Our findings highlight the importance of lower limb stiffness in the context of muscular power production during multi-joint tasks. They let us speculate that during adolescence, children acquire the ability to take greater advantage of plastic energy storage in the musculotendinous system when performing maximum counter-movement jumps.